In Silico Molecular Docking and ADMET Analysis for Drug Development of Phytoestrogens Compound with Its Evaluation of Neurodegenerative Diseases - Faisal Akhmal Muslikh; Reyhan Rahma Samudra; Burhan Ma’arif; Zulvikar Syambani Ulhaq; Suko Hardjono; Mangestuti Agil (Borneo Journal of Pharmacy, 2022)
Neurodegenerative disease is one of the problems faced by postmenopausal women due to estrogen deficiency. Phytoestrogen compounds can be used as an alternative treatment for diseases caused by estrogen deficiency by binding to their receptors through the estrogen receptor (ER) dependent pathway. With in silico studies, this study aims to predict how phytoestrogen compounds will stop neurons from dying by using the dependent ER pathway. Genistein, daidzein, glycitein, formononetin, biochanin A, equol, pinoresinol, 4-methoxypinoresinol, eudesmin, α-amyrin, and β-amyrin compounds were prepared with ChemDraw Ultra 12.0. Then their pharmacokinetic and pharmacodynamic properties were examined using SwissADME. Geometry optimization of the compound was performed using Avogadro 1.0.1, and molecular docking of the compound to the ERα (1A52) and ERβ (5TOA) receptors was performed using AutoDock vina (PyRx 0.8). The interaction visualization stage was carried out with Biovia Discover Studio 2021, while the toxicity values of the compounds were analyzed using pkCSM and ProTox II. The results showed that the equol compound met the pharmacokinetic, pharmacodynamic, toxicity criteria, and had similarities with the native ligand 17β-estradiol. Equol compound inhibits neurodegeneration via an ER-dependent pathway by binding to ERα (1A52) and ERβ (5TOA) receptors.